Pelatihan Pembuatan Sabun Cair dengan Penambahan Ekstrak Tanaman Lahan Rawa Gambut Galam (Melaleuca leucadendron Linn.) dan Telang Ternate (Clitoria ternatea) bagi Siswa SMK 1 Palangka Raya: Training on Making Liquid Soap with the Addition of Galam Peat Swamp Plant Extract (Melaleuca leucadendron Linn.) and Ternate Telang (Clitoria ternatea) for SMK 1 Palangka Raya Students - Nursiah, Nursiah; Putir, Patrisia Erosa; Madiyawati, Milad; Rosdiana, Rosdiana; Maryani, Maryani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Soap on the market is purchased as a household necessity at a cheap or affordable cost. However, if you calculate the total cost of purchasing soap with the frequency of washing dishes and clothes for each family for an unlimited amount of time and for a long time, this will result in quite a large amount of expenditure for the family every month. Therefore, additional income is needed that can improve the family's economy. Based on this, the aim of implementing the community service program under the Community Entrepreneurial Assistant Lecturer Program (PDPWM) is to increase the insight and skills of students (i) SMKN 1 Palangka Raya regarding plants. local medicine typical of Central Kalimantan through counseling on the Introduction and Utilization of Local Medicinal Plants Typical of Central Kalimantan, namely the Galam Plant (Melaleuca leucadendron Linn.) as a fragrance and Ternate Telang (Clitoria ternatea) as a natural coloring in soap making. Training on making liquid hand-washing soap for students of SMKN 1 Palangka Raya has been successfully implemented. The output of this training is a liquid hand-washing soap product packaged in plastic bottles. Another result is the acquisition of knowledge regarding soap making along with the practices carried out by service activity participants